HOW TO EVALUATE FINANCIAL LIQUIDITY OF A COMPANY USING THE DISCRIMINANT ANALYSIS - Bolek, Monika; Grosicki, Bartosz (European Scientific Journal, ESJ, 2015)
In this paper authors analyse the problem of liquidity evaluation in a company and come to the conclusion that there are many approaches to this phenomena and it is difficult to conclude if the company situation in this field is good or not. Managers can wait until the bankruptcy moment when it is known for sure that there is no liquidity in a company or they can check it and act earlier. Many companies are falling and many are operating on the edge since managers are not able to focus on every liquidity aspect simultaneously. With the model proposed in this paper, based on the discriminant analysis, it is possible to evaluate the company liquidity situation and improve it if necessary.